STUDENTS’ PERCEPTIONS OF INSTAGRAM CAPTION AS MEDIA IN ENGLISH LANGUAGE TEACHING - Ade Christanty Yudha Bestari (Universitas Perjuangan Tasikmalaya, 2020)
Everybody has Instagram account in this digital era. The lecturer uses Instagram as the media in English Language Teaching. The lecturer asks the students to write their idea in English as Instagram caption. This study presents the students’ perceptions of using social media, Instagram. All the participants in this study are students of Mathematic Study Program who enroll in English class at Nahdlatul Ulama University Purwokerto. The data were analyzed by using both quantitative and qualitative method. The data taken from survey through questionnaire were analyzed quantitatively. Then, the researcher used qualitative analysis to present the data from interview. The finding showed that the students’ perceived the advantages and disadvantages of using Instagram caption. The advantages showed that the participants have a positive perception of Instagram caption as a media in English Language Teaching. First, it stimulated the students to develop positive attitude in creative writing. Second, it improved students’ grammatical competences. The last, it enhanced the students’ motivation in English writing. Three disadvantages of using instagram as a media in teaching English included internet connection problem, low engagement rate of students’ in Instagram, and language barrier. Some of the students still used Google Translate (GT) to ensure that their sentences were correct. Keywords: Students’ Perceptions, Instagram, English Language Teaching